Caring for Moderate to Severe Dementia Patients - Malaysian Family Caregivers Experience - AM, Zuria Idura; MT, Noorlaili; R, Rosdinom; B, Azlin; MD, Tuti Iryani (IIUM Medical Journal Malaysia, 2018)
Introduction: Caring for those with dementia affects the quality of life for both the caregivers and the patients themselves, particularly in the informal care system here in Malaysia. To date, only a few studies have explored from the family caregivers’ perspectives in the communities of different cultural background. The purpose of this study is to describe the Malaysian family caregivers’ perspectives of their experiences in providing care to for their family members suffering from moderate to severe dementia in Kuala Lumpur, Malaysia. Methods: This qualitative study involved in-depth individual interviews with twelve caregivers to patients with moderate to severe dementia. Participants were recruited via purposive sampling from the outpatient psycho-geriatric clinic at UKM Medical Centre, Kuala Lumpur. All interviews were audio-recorded and transcribed verbatim. Transcribed data was later analysed using a thematic approach. Results: Four themes identified in this study were; i) the feeling that ‘it is like caring for a baby’, ii) the caregivers’ perception of inadequate knowledge and skills, iii) the need for caregivers’ support system and iv) the importance of spirituality in enhancing care giving experiences. Conclusions: The framework of care shared by the caregivers in this study demonstrated strong cultural and spirituality influences in addition to the common issues of the challenges in managing the behavioural and psychological symptoms in people with dementia. Hence, culture and spirituality aspects should be addressed in the development of appropriate intervention to manage the needs of informal caregivers in this community.